Fathers of Children With Type 1 Diabetes: Perceptions of a Father's Involvement From a Health Promotion Perspective. (August 2014) - Boman, Åse; Povlsen, Lene; Dahlborg-Lyckhage, Elisabeth; Hanas, Ragnar; Borup, Ina K.
This study describes how fathers of children diagnosed with type 1 diabetes understand their involvement in their child's daily life from a health promotion perspective. Sixteen Swedish fathers of children living with type 1 diabetes were interviewed. Manifest and latent content analysis was used to identify two themes: the inner core of the father's general parental involvement and the additional involvement based on the child's diabetes. The former was underpinned by the fathers' prioritization of family life and the fathers being consciously involved in raising the child, and the latter by the fathers promoting and controlling the child's health and promoting and enabling the child's autonomy. The results highlight that the quality of the fathers' involvement is essential in the management of a child's chronic illness. It is important for pediatric diabetes health care professionals to assess the quality of fathers' involvement to promote the child's health.